IMPLEMENTATION OF PSAK 107 IJARAH ACCOUNTING AT ISLAMIC MICROFINANCE INSTITUTIONS - Sholeh, Alvin Firdaus; Kholilah, Kholilah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to analyze the implementation of the ijarah agreement in bai al wafa financing at BMT X. An ijarah contract is a rental transaction for goods or services between the owner of the rental object and the lessee to receive compensation for the asset being leased. This research uses the ijarah product object of bai al wafa financing at BMT X. The research method used in this research is qualitative method. This research concludes that the implementation of the ijarah agreement for bai al wafa financing carried out by BMT is according to the applicable principles of ijarah implementation in Indonesia and the accounting practice is entirely by the provisions in PSAK 107.